Accreditation in Higher Education in Brazil: Notes from the legal devices of education in Brazil (2022)
In the Brazilian legal system, the term accreditation does not appear as a legal device. The terms used by the Brazilian legislation, whether for institutions, courses, programs, or academic degrees, are operation authorization, recognition, accreditation, recredentialing, and evaluation, carried out by the public power. The authorization verifies the suitability of an educational institution, public or private, to offer quality education. The recognition confirms (or not) this suitability. Accreditation verifies the institutional conditions of supply. The evaluation measures the adequacy of this set to the quality standard, a principle of education demanded by the Constitution. Accreditation is a non-statal process that, under the direction of private or governmental entities or Professional Councils, seeks quality control of professionals, of services rendered or products, under national or international technical standards (ISO, regulatory agencies, professional councils). In general, such entities evaluate quality by issuing a certification that verifies the quality of the service provided by professionals in practice, of services provided to users, or of products sold in the market. In this sense, accreditation is an ex-post academic-institutional certification that seeks to ensure the ability of these institutions to provide their graduates with quality standards.